1998
DOI: 10.1086/517367
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Response to the 60‐kDa Chlamydial Heat‐Shock Protein Is Associated with Scarring Trachoma

Abstract: To determine if serum antibody response to the 60-kDa chlamydial heat-shock protein (Chsp60) was associated with scarring trachoma, responses to Chlamydia trachomatis and to Chsp60 from 148 Gambian subjects with trachomatous scarring and from 148 controls without clinical evidence of disease from trachoma-endemic communities were characterized. Chsp60 response was found in 32% of cases and 16% of controls (P < .001). Although C. trachomatis titer was also higher in cases than controls, the prevalence of Chsp60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
1
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(53 citation statements)
references
References 14 publications
1
50
1
1
Order By: Relevance
“…Some have proposed that IFNg-induced chlamydial persistence may lead to chronic inflammation and tissue damage 36,37 partly through the induction of putative sensitizing antigens such as chlamydial heat shock protein 60 (Chsp60). 38 Antibodies to Chsp60 have been found to be associated with scarring sequelae of chlamydial infection in the eye and the genital tract, 39,40 and it has been shown that IFNg is capable of mediating overexpression of Hsp 60 in vitro in HeLa cells. 37 The role of this IFNg-mediated induction of Hsp 60 in vivo has not been established.…”
Section: Discussionmentioning
confidence: 99%
“…Some have proposed that IFNg-induced chlamydial persistence may lead to chronic inflammation and tissue damage 36,37 partly through the induction of putative sensitizing antigens such as chlamydial heat shock protein 60 (Chsp60). 38 Antibodies to Chsp60 have been found to be associated with scarring sequelae of chlamydial infection in the eye and the genital tract, 39,40 and it has been shown that IFNg is capable of mediating overexpression of Hsp 60 in vitro in HeLa cells. 37 The role of this IFNg-mediated induction of Hsp 60 in vivo has not been established.…”
Section: Discussionmentioning
confidence: 99%
“…4 -6 Chlamydial Hsp60 seroreactivity has also been previously implicated in the pathogenesis of chlamydial infections and in the development of severe sequelae after infections. 11,12,[21][22][23][24][25] It has also been directly linked to the pathogenesis of atherosclerosis, 14,26 and quite recently a strong correlation between anti-Hsp60 IgG levels and coronary heart disease was reported. 27 It has therefore been suggested that Hsps may be the link between C pneumoniae infections and atherogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The levels of chlamydial HSP60 antibodies are predictive for an increased risk of pelvic inflammatory disease in women [18]. They also correlate with other pathologic sequelae of C. trachomatis infections, such as tubal factor infertility, habitual abortion, endometriosis, ectopic pregnancy [19±24], and scarring trachoma [25]. Only a few reports have thus far been published of the antibody response to C. pneumoniae HSP60 [26±29].…”
Section: Hsp60 Antibodies and Pathogenesis Of Chlamydial Diseasesmentioning
confidence: 99%